Teachers' Instructional Practices for Promoting Primary One Learners' Mathematics Competence: A Comparative Study of Busiro and Luuka, Uganda - Kisa, Sarah; Ejuu, Godfrey; Asiimwe, Joyce Ayikoru (American Journal of Education and Practice, 2020)
Purpose: Mathematics is a globally compulsory school subject and plays a fundamental role in an individual's daily life activities. Elementary school teachers' instructional practices are key in fostering among learners the foundational competences in basic number operations. This study explored the instructional practices Primary One teachers in Busiro North and Luuka North Counties can adopt from each other in order to enhance their learners' mathematics competence. Methodology: A qualitative approach with an observational multiple case study design was employed to obtain data from 74 purposively selected teachers. Data was collected through non-participant observation. Each teacher was observed teaching mathematics to Primary One learners and interviewed after the lesson. Data obtained was analysed descriptively. Findings: Findings indicate that teachers use songs, rhymes and games involving mathematical concepts, in both English language and the local languages to help learners attain competence. Teachers have also embraced use of locally available materials like woven plastic propylene bags (buveera) and banana fibres to make and decorate charts in the classrooms' mathematics learning areas. Attention grabbers like "Good children, Good teacher"; "We, Work"; are common verbal interactions between teacher and learners when the class seems to lose concentration. Teachers recognise learners' efforts when they correctly answer oral, written or practical tasks by asking the class to give a classmate "flowers" or "the pa-pa-pa clap". Unique contribution to theory, practice and policy: For teachers to help learners' master mathematical concepts and augment their competence, they should build on learners' experience and prior knowledge, give learners opportunities to explain their mathematical ideas and use the think - pair - share strategy during problem solving.